Diferentes abordagens para o manejo das águas pluviais e seus impactos no ciclo de vida em loteamento de interesse social - Santos, Maria Fernanda Nóbrega dos (Universidade Federal de São Carlos, 2018)
Stormwater-derived problems in urban settlements are occurring more frequently and intensely, particularly in developing countries, where cities are growing without planned implementation. Coupled with the current water quality decline, this makes it more urgent to reconsider the way in which stormwater management is conceived and implemented in urban allotments. In this context, strategies proposed by low impact development (LID) integrated approach, stand out as an alternative to conventional systems. LID promotes stormwater management aligned with urban planning and, as a main goal, regulates hydrological processes in their origin. However, if minimized impact on urban basins is one of the fundamental purposes of stormwater management systems, it will be necessary to consider the wider implications when choosing the most appropriate approach. This study’s objective is to develop a multidimensional evaluation (hydrological, environmental, and economic) from a life cycle perspective, which should make it possible to compare different strategies for stormwater management in urban settlements. As such, an area located in the municipality of São Carlos/SP (the settlement Américo Alves Margarido) was used as a study object and three scenarios of occupation and stormwater management systems were designed: Scen.CONV, a conventional urbanization plan and storm-sewer drainage-system; Scen.WELL, a conventional urbanization plan associated with the use of infiltration wells to disconnect lots; and Scen.LID, which uses structural (vegetative swales and infiltration trenches) and nonstructural strategies (such as land use/imperviousness coefficients and urban changes). For a comparative analysis, these scenarios were modeled in storm water management model (SWMM), and both life cycle assessment (LCA), and life cycle costing (LCC) were performed. According to the results, hydraulic-hydrologic modeling indicated a decrease of 60% in the peak flow of Scen.WELL compared to Scen.CONV, potential impact per m³ of stormwater volume managed in Scen.Well that was 51–65% lower, and costs per m³ that were 54–58% lower than in Scen.CONV. In Scen.LID it was possible to achieve pre-development conditions, with a decrease of 100% in the peak flow compared to Scen.CONV. Scen.LID costs per m³ were 71–79% lower, and potential impacts per m³ 74–82% lower than in Scen.CONV, also for all impact categories.
Keywords: Sistemas de manejo de águas pluviais; Desenvolvimento de baixo impacto; Modelagem hidrológica; Custeio do ciclo de vida; Avaliação do ciclo de vida; Stormwater management systems; Low impact development; Hydrological modeling; Life cycle costing; Life cycle assessment; ENGENHARIAS::ENGENHARIA CIVIL; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::DRENAGEM URBANA DE AGUAS PLUVIAIS